2017
DOI: 10.1371/journal.pntd.0006091
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms associated with adverse dengue fever prognoses at the time of reporting in the 2015 dengue outbreak in Taiwan

Abstract: BackgroundTainan experienced the most severe dengue epidemic in Taiwan in 2015. This study investigates the association between the signs and symptoms at the time of reporting with the adverse dengue prognoses.MethodsA descriptive study was conducted using secondary data from the Dengue Disease Reporting System in Tainan, Taiwan, between January 1 and December 31, 2015. A multivariate stepwise logistic regression was used to identify the risk factors for the adverse prognoses: ICU admissions and mortality.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
0
25
1
1
Order By: Relevance
“…Many studies in Taiwan show that the elderly had a higher prevalence rate than those in younger dengue patients, which was in contrast to other Southeast Asian countries [ 52 , 53 , 54 ]. The length of time that people spend in green spaces may be an important factor that affects incidence of DF.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies in Taiwan show that the elderly had a higher prevalence rate than those in younger dengue patients, which was in contrast to other Southeast Asian countries [ 52 , 53 , 54 ]. The length of time that people spend in green spaces may be an important factor that affects incidence of DF.…”
Section: Discussionmentioning
confidence: 88%
“…Infeksi dengue memberikan beban eko o i terutama negara endemis n m di dengan sumber daya yang minim. [1][2][3] Dem am Berdarah Deng u e ( DB D) merupakan bentuk manifestasi infeksi dengue. DBD diperkirakan masih akan cenderung meningkat dan penyebarannya bertambah luas.…”
Section: Abstract / a B S T R A Kunclassified
“…The risk factors associated with increased severity and fatal outcomes have been addressed in previous studies [ 15 , 16 , 17 , 18 , 19 ]. A study from Taiwan has shown that old age, respiratory distress, altered consciousness, and thrombocytopenia were significantly associated with the risk of mortality [ 15 ]. A study from Brazil reported that age >55 years, gastrointestinal bleeding, hematuria, and thrombocytopenia were independently associated with mortality [ 16 ].…”
Section: Introductionmentioning
confidence: 99%